La investigación española en Teoría de la Documentación (1990-2000). - López Yepes, José (Revista General de Información y Documentación, 2001)
A historical review of the salient points aud trends in the evolution and the studies in Documentation theory in the 1 990s in Spain. The author brings aout the fact that this isa kind of década prodigiosa on account of the importantevents which have taken place in the different aseas of our spbere of interest. Among these are: the creation of the Licenciate and Doctorate in Documentation, the appearance of new journals in the field, the publication of studies concerning the assessment of our research,
Keywords: Documentation Theory; research; terminology; medical documentation; informative documentation